Suicide but Jack was a good driver. - CRM Educational Films (Del Mar, Calif. : CRM/McGraw-Hill Films, 1974)
Suicide by young people is at an alarmingly high rate; perhaps because their pain and guilt often go unreleased or unrecognized. This film will open this sensitive subject for discussion.
Keywords: Suicide -- In adolescence